The Study of Information Seeking Behavior of Allameh Tabataba’i University Faculty Members in Using Online Resources - Mosa Majidi; Ghorban Shakerian (بازیابی دانش و نظام‌های معنایی, 2016)
The main objective of this study was to evaluate the information seeking behavior of academic staff in the use of online resources at Tabataba’i University. The methodology of this study is a descriptive survey and a research application was implemented.  The instrument used for data collection questionnaire was developed and distributed among the 472 members of the faculty at Allameh Tabataba’i University. The results show that 80 percent of faculty members through the Internet search and online sources are familiar with the individual studies and their main goal is conducting research into the use of online resources and up to date information. In a variety of magazines, online resources and electronic books more than other types of applications. Eighty eight percent of Allameh Tabataba’i University faculty members use free information resources to meet the needs of their own. The main criteria for the evaluation of the new and updated information are available online resources. According to the results, the biggest difficulties experienced by the fellow members of university staff in using online resources include the constant inaccessibility of information banks owing to the lack of a comprehensive policy in this respect and the very low speed of the Internet.